Disorders of vision in neonatal hypoxic-ischaemic encephalopathy: a systematic review. Issue 4 (27th November 2020) - Nagy, Eva; Self, Jay; Williams, Cathy; Vollmer, Brigitte
Abstract : Objective: Neonatal hypoxic-ischaemic encephalopathy (HIE) following perinatal asphyxia in term infants is associated with neonatal mortality and a high risk of neurodevelopmental impairment later in life. Visual disorders are an accepted complication of HIE and the association has been cited in the literature many times. This review aims to study the evidence for this association and assess the quality of the data on which this is based. Design: A systematic literature review was conducted and 922 citations were assessed using standard methods outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol. Results: The results demonstrate that the majority of studies have reported on various neurodevelopmental outcomes but rarely specifically vision. Based on limited currently available data, extracted from a number of small studies, an association of neonatal HIE with visual impairments seems to exist but detail is lacking. Notably, in the existing studies, there is a striking lack of consistency in the methods used to diagnose HIE and, similarly, a wide variation in the methods employed to measure visual function. Conclusions: To explore the observed association further in terms of prognosis and the effects of HIE treatments on visual outcomes, future studies will need to address the issues of standardised diagnostic criteria, severity grading and robust, age-appropriate visual assessment.